INFLUENCE OF TRANSMITTER NONLINEARITIES ON DATA TRANSMISSION FROM REMOTELY PILOTED AIR SYSTEM - Grekhov, Andrii; Kondratiuk, Vasil; Ermakov, Anton; Chernyuk, Evgen (Proceedings of National Aviation University (archive), 2017)
Purpose: 1) to develop a model of a communication channel of an unmanned aerial vehicle "UAV-Ground station" with adaptive modulation and orthogonal frequency division of channels; 2) to calculate the channel parameters with different types of fading for different levels of satellite transponder nonlinearity. Method: MATLAB Simulink software was used to simulate the channel operation. Results: Based on the IEEE 802.16d standard, a realistic model of the communication channel of the unmanned aerial vehicle "UAV-Ground Station" was developed, which is used to estimate the channel parameters. The channel model with adaptive modulation consists of a source of information, a transmitter, a downlink channel with fading, and a terrestrial station receiver. Dependences of the signal-to-noise ratio of the terrestrial receiver on the signal-to-noise ratio in the channel down for different types of nonlinearity of the unmanned aerial transmitter, various modulations (BPSK, QPSK, 16QAM, 64QAM), various types of fading are obtained. The signal constellations of the received signals for different Doppler frequency shifts are compared. Conclusion: The developed model allows determining the conditions under which the channel is "open" for a given type of a modulation and a data rate. The proposed approach can be considered as a method for estimating the parameters of the satellite communication channel of an unmanned aerial vehicle with fading.